(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In this paper, the problem of robust delay-dependent stability criterion is considered for a class of linear continuous time heat exchanger system with constant additive state-delays and bounded nonlinear perturbations using Lyapunov-Krasovskii (LK) functional approach. In the proposed delay-dependent stability analysis, the time-delays are considered to be time-invariant. In the proposed delay-dependent stability analysis, a candidate LK functional is considered, and take the time-derivative of the functional is bounded using the Jenson integral inequality. The proposed stability analysis finally culminates into a stability criterion in LMI framework. The effectiveness of the proposed stability criterion is illustrated using a network controlled temperature control of heat exchanger system